PENGARUH INFRASTRUKTUR E-SPORTS TERHADAP PERTUMBUHAN EKONOMI NEGARA ASIA TENGGARA - Ramadhan, Rahmat; Merlinda, Santi (Bina Ekonomi, 2024)
This research discusses the influence of  infrastructure as a supporting factor for economic growth in Southeast Asian countries. This research uses a quantitative approach with data collection techniques through literature study. The data used is from 2016 to 2022. The independent variable data used in this research are: Number of Mobile Legends Players, Number of Mobile Legends Venues and Information and Communication Technology Development Index in Southeast Asian Countries. Then the dependent variable is National Income in Southeast Asian Countries. The research results show that the number of players variable has a significant effect on national income, the number of venues has no significant effect on national income, and the information and communication technology development index variable has a significant effect on the national income variable. Then, if viewed simultaneously, the variables number of players, number of venues and the information and communication technology development index on simultaneous have a significant effect on national income. These three variables have an influence on national income of 68%, while the deficiency of 32% is influenced by other variables outside the research.